Metodología docente y evaluación por competencias: una experiencia en la materia Dirección de Producción - María Luz Martín-Pe\~na; Eloísa Díaz-Garrido; del Barrio Izquierdo Luis (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2012)
– The design of the new study plans adapted to the guidelines of the European Higher Education Area (EHEA) attempt to bring business reality closer to the students, involving them into their learning process adopting an active model and participation and providing them a favourable framework in order to gain different skills. This requires designing more active teaching methodologies and setting up a capable assessment model to assess the skills obtained by students. The purpose of this paper is double, the first one, it is expected to identify the learning methods to achieve skills acquisition defined for the Production Management field in the EHEA framework, and the second one, explaining a capable skills assessment model. The empirical analysis developed has proved the teaching methods effectiveness used in the lecture rooms, but also show the importance of the skills assessment properly, what permit to gain the EHEA basic purpose.
Keywords: M11; M19; I23; 650; production and operations management; teaching methodology; skills; European higher education area